A comparative analysis of microsurgical resection versus stereotactic radiosurgery for Spetzler-Martin grade III arteriovenous malformations: a multicenter propensity score matched study - Tos, Salem; Hajikarimloo, Bardia; Osama, Mahmoud; Mantziaris, Georgios; Adeeb, Nimer; Kandregula, Sandeep; Salim, Hamza Adel; Musmar, Basel; Ogilvy, Christopher; Kondziolka, Douglas; Dmytriw, Adam A.; El Naamani, Kareem; et al. (Clinical neurology and neurosurgery, 2025)
Background - Spetzler-Martin (SM) Grade III brain arteriovenous malformations (BAVMs) represent a transitional risk zone between low- and high-grade BAVMs, characterized by diverse angioarchitecture. The primary treatment options are endovascular embolization, microsurgical resection (MS), and stereotactic radiosurgery (SRS). This study compares the efficacy and outcomes of MS and SRS. - Methods - We conducted a multicenter, retrospective study involving patients from the MISTA database with SM Grade III BAVMs treated with MS or SRS between 2010 and 2023. Propensity matching was based on age, favorable modified Rankin Score (mRS) at presentation, nidus size, rupture status, location depth, and eloquence. - Results - After matching, 60 patients were equally divided between MS and SRS groups. Median age (MS: 45.0 vs. SRS: 42.5 years, p=0.3) and AVM size (MS: 3.2 vs. SRS: 2.9cm3, p=0.6) were similar. MS showed higher obliteration rates (93.3%) compared to SRS (46.7%) at the last follow-up (p<0.001). The median time to obliteration post-SRS was 31.5 months (IQR: 15.3-60.0). SRS obliteration rates were 19%, 29%, and 59% at 24, 36, and 60 months, respectively. Overall complication rates (MS: 30% vs. SRS: 20%, p=0.4) and permanent complications (MS: 10% vs. SRS: 13.3%, p>0.9) were similar. Hemorrhage occurred once in the MS group and none in the SRS (p>0.9). Favorable outcomes (mRS 0-2) were higher with SRS than MS (93.3% vs 80.0%, p=0.3), with one AVM-related mortality in the MS group. - Conclusion - MS and SRS are viable treatments for SM Grade III BAVMs. Treatment choice should be individualized by a multidisciplinary team, considering patient goals.
Online verfügbar: 3. Dezember 2024, Artikelversion: 5. Dezember 2024
Gesehen am 11.06.2025